Upaya Peningkatan Keaktifan Belajar Peserta Didik Menggunakan Model Problem Based Learning (PBL) dengan Strategi Berdiferensiasi - Nurhalimah Nurhalimah; Meilinda Meilinda (Ideguru: Jurnal Karya Ilmiah Guru, 2023)
Based on the results of pre-cycle observations, it is known that the learning activity of students in class XI MIA 2 SMAN 10 Palembang is still in the low category. So we need a strategy to increase the active learning. This research was conducted as an action to increase the active learning of students using the PBL model with a differentiation strategy. This research is a classroom action research carried out in two cycles and each cycle consists of 3 stages, namely action planning, action implementation and reflection. Research data was collected by means of observation by 5 observers of 30 students. Then the data were analyzed by comparing the results of observations in pre-cycle, cycle 1 and cycle 2. From the observation results it is known that there is an increase in student learning activity from 51.36% (pre-cycle), increasing to 58.75% (average cycle 1) and then increasing to 77.5% (average cycle 2), so it can be concluded that the PBL model with a differentiation strategy can increase the activeness of students. This research can be used as a reference for educators in increasing the activity of students in class.